IQ-domain GTPase-activating protein 1 promotes the malignant phenotype of invasive ductal breast carcinoma via canonical Wnt pathway. Issue 6 (May 2017) - Zhao, Huan-Yu; Han, Yang; Wang, Jian; Yang, Lian-He; Zheng, Xiao-Ying; Du, Jiang; Wu, Guang-Ping; Wang, En-Hua
IQ-domain GTPase-activating protein 1 is a scaffolding protein with multidomain which plays a role in modulating dishevelled (Dvl) nuclear translocation in canonical Wnt pathway. However, the biological function and mechanism of IQ-domain GTPase-activating protein 1 in invasive ductal carcinoma (IDC) remain unknown. In this study, we found that IQ-domain GTPase-activating protein 1 expression was elevated in invasive ductal carcinoma, which was positively correlated with tumor grade, lymphatic metastasis, and poor prognosis. Coexpression of IQ-domain GTPase-activating protein 1 and Dvl in the nucleus and cytoplasm of invasive ductal carcinoma was significantly correlated but not in the membrane. Postoperative survival in the patients with their coexpression in the nucleus and cytoplasm was obviously lower than that without coexpression. The positive expression rates of c-myc and cyclin D1 were significantly higher in the patients with nuclear coexpression of Dvl and IQ-domain GTPase-activating protein 1 than that with cytoplasmic coexpression, correlating with poor prognosis. IQ-domain GTPase-activating protein 1 significantly enhanced cell proliferation and invasion in invasive ductal carcinoma cell lines by interacting with Dvl in cytoplasm to promote Dvl nuclear translocation so as to upregulate the expression of c-myc and cyclin D1. Collectively, our data suggest that IQ-domain GTPase-activating protein 1 may promote the malignant phenotype of invasive ductal carcinoma via canonical Wnt signaling, and it could be used as a potential prognostic biomarker for breast cancer patients.